ANALISIS TAQAB AL-AKHTHA DALAM PEMBELAJARAN BAHASA ARAB KELAS 11 DI SMA IT AL-HUDA - Habiburahman; Fadhli Hafizh; Muhammad Zuhal Wardhana; Fajar Abdurrahman; Zulli Umri Siregar (PT. Hasba Edukasi Mandiri, 2026)
This study aims to analyze taqāb al-akhtā’ (error classification) in Arabic language learning among eleventh-grade students at SMA IT Al-Huda. The research employs a qualitative approach with a descriptive-analytical design. The data were collected from students’ written assignments, daily exercises, and Arabic language assessments conducted over one academic semester. Data collection techniques included documentation and non-participant observation, while data analysis followed the error analysis framework consisting of error identification, classification, description, and interpretation of error sources. The findings reveal that students’ Arabic language errors occur systematically and recurrently, with syntactic errors (naḥw) as the most dominant category, followed by morphological errors (ṣarf), misuse of particles, and orthographic errors. These errors are influenced by mother tongue interference, overgeneralization of grammatical rules, limited mastery of Arabic structures, and learning approaches that emphasize mechanical rule memorization. From the interlanguage perspective, the identified errors represent a developing linguistic system constructed by learners during the process of acquiring Arabic as a foreign language. This study highlights the pedagogical significance of error analysis as a reflective tool in Arabic language instruction. The results are expected to contribute theoretically to error analysis studies and practically to the development of more adaptive and contextual Arabic language teaching strategies.